A Selection Model to Logistic Centers Based on TOPSIS and MCGP Methods: The Case of Airline Industry - Kou-Huang Chen; Chin-Nung Liao; Li-Chun Wu (Journal of Applied Mathematics)
The location selection of a logistics center is a crucial decision relating to cost and benefit analysis in airline industry. However, it is difficult to be solved because there are many conflicting and multiple objectives in location problems. To solve the problem, this paper integrates fuzzy technique for order preference by similarity to an ideal solution (TOPSIS) and multichoice goal programming (MCGP) to obtain an appropriate logistics center from many alternative locations for airline industry. The proposed method in this paper will offer the decision makers (DMs) to set multiple aspiration levels for the decision criteria. A numerical example of application is also presented.